In Silico, In Vitro, and In Vivo Wound Healing Activity of Astragalus microcephalus Willd. (4th October 2022) - Akbari, Fatemeh; Azadbakht, Mohammad; Bagheri, Ali; Vahedi, Lale
Abstract : Background and Objectives. A wound is one of the high-prevalence disorders that affect people's lives physically, mentally, and financially. This study examined the Astragalus microcephalus Willd. wound healing process in in vivo and in vitro conditions by focusing on the phytoestrogen activity of this extract. Methods . The methanolic root extract was prepared by maceration, and flavonoids were evaluated by LC/MS. In silico examination was performed based on the LC/MS results, and the binding affinity of these compounds to estrogen receptors (ERs) α and β was evaluated. Wound healing evaluation in both in vitro (NHDF cell line, by 500  μ g/ml concentration of the extract, 24 h) and in vivo (Wistar rat, topical daily treated with 1.5% of the extract ointment, 21 days) conditions in comparison to control groups was conducted. Rats' control groups included silver sulfadiazine, Vaseline, and the nontreated groups. Results . Eleven flavonoids were detected using LC/MS. The in silico study showed that formononetin, kaempferol-based structures, quercetin-3-O-neohesperidoside, and calycosin-7-O-beta-D-glucoside had a high affinity (<−6.3) to ERs α and β . Wound closing measurement showed significant improvement in the group treated with the extract in both in vitro and in vivo assays compared to the control groups. Histopathological results confirmed these findings; inflammation factors decreased, and fibroblast proliferation, fibrosis, and epithelization increased, especially in the extract group. Conclusion . This study shows that Astragalus microcephalus has wound healing activity in vitro and in vivo with low toxicity due to the presence of flavonoids, especially isoflavonoids, which show a high affinity to bind to ERs α and β in the skin tissue.